2017
DOI: 10.1159/000484031
|View full text |Cite
|
Sign up to set email alerts
|

Leonurine Prevents Atherosclerosis Via Promoting the Expression of ABCA1 and ABCG1 in a Pparγ/Lxrα Signaling Pathway-Dependent Manner

Abstract: Background/Aims: Previous studies have demonstrated that leonurine, a unique alkaloid compound of Herba leonuri, can exert anti-oxidative and anti-inflammatory effects on the development of atherosclerosis (AS). This study was designed to investigate the effects of leonurine on cholesterol efflux from THP-1 macrophage-derived foam cells and development of atherosclerotic lesions in apoE-/- mice, and further determine the potential mechanisms. Methods: Human THP-1 cells were fully differentiated into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 65 publications
0
50
0
Order By: Relevance
“…(Suguro et al, 2018) PPAR γ /LXRα pathway is thought to be involved in the protective role of LEO against atherosclerosis. (Jiang et al, 2017) Encouraged by emerging evidence of its effectiveness and safety in preclinical studies reported by our team and other labs, we have initiated clinical transformation research of LEO since last year. At present, it has passed the safety test of phase I clinical experiment.…”
Section: Downloaded Frommentioning
confidence: 99%
“…(Suguro et al, 2018) PPAR γ /LXRα pathway is thought to be involved in the protective role of LEO against atherosclerosis. (Jiang et al, 2017) Encouraged by emerging evidence of its effectiveness and safety in preclinical studies reported by our team and other labs, we have initiated clinical transformation research of LEO since last year. At present, it has passed the safety test of phase I clinical experiment.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Four of these studies were excluded because atherosclerosis lesion area was not reported (Ching et al, 2013 ; Wang et al, 2015 ; Li et al, 2016 ; Yang et al, 2017 ), one study was excluded because a mixture of herbal medicines was administered (Ho et al, 2012 ), and one study was excluded for intervention combining with surgery (Son et al, 2012 ). At last, 14 eligible studies were included in this systematic review (Wang et al, 2011 ; Ching et al, 2012 ; Fujiwara et al, 2012 ; Mercer et al, 2012 ; Cai et al, 2013 ; Wei et al, 2013 ; Zhuang et al, 2013 ; Chen et al, 2014 ; Xu et al, 2014 ; Feng et al, 2017a , b ; Jiang et al, 2017 ; Liu et al, 2017 ; Zhu et al, 2018 ), of which studies (total 21 animal experiments and 331 animals involved) could be embodied in the meta-analysis (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Only three studies used female animals, eight used male, and three studies didn't mention the gender of animals in their experiments. Mice received a normal-chow diet in five studies (Ching et al, 2012 ; Fujiwara et al, 2012 ; Mercer et al, 2012 ; Wei et al, 2013 ; Jiang et al, 2017 ); a high fat diet in nine studies containing either 21% fat and 1.25% cholesterol (Feng et al, 2017a , b ), 42% fat and 0.2% cholesterol (Zhu et al, 2018 ), 32% fat and 1% cholesterol (Chen et al, 2014 ), 20% fat and 0.15% cholesterol (Xu et al, 2014 ), 16.6% fat, 10.6% sucrose and 1.3% cholesterol (Zhuang et al, 2013 ), the D12079B diet (Research Diets Inc,), containing 21% fat and 0.21% cholesterol (Wang et al, 2011 ), the D12108C diet (Research Diets Inc,), containing 20% fat and 1.25% cholesterol (Cai et al, 2013 ), and unmarked fat and cholesterol content (Liu et al, 2017 ). Administration timing and duration of alkaloids varied greatly.…”
Section: Resultsmentioning
confidence: 99%
“…ABCG1 increases the availability of cholesterol to a variety of extracellular lipoprotein acceptors, including HDL and LDL . A series of studies have shown that ABCG1 can regulate cellular cholesterol efflux, and decreased ABCG1 in atherosclerotic lesions aggravates lipid accumulation and leads to foam cell formation . Ox‐LDL reduces ABCG1 expression in VSMCs, although its mechanism needs to be further explored .…”
Section: Discussionmentioning
confidence: 99%